A CRITICAL STUDY OF LANDMARK CASES IN THE LEGAL PROTECTION OF MEDICAL PERSONNEL AND PATIENTS IN INDONESIA - Widjaja, Gunawan (Berajah Journal, 2025)
This study critically examines legal regulations related to the protection of medical personnel and patients in Indonesia, focusing on landmark cases that reflect legal challenges in the healthcare sector. The study found that although legal protections for medical personnel and patients are set out in legislation, implementation is often hampered, particularly in the context of medical decision-making, malpractice risks and lawsuits. Lack of legal certainty for medical personnel can hamper their professionalism, while for patients, unclear rights to quality services can reduce trust in the health system. Through the analysis of various cases in the literature review, this study identifies the need for legal reforms that focus on balancing the rights and obligations of both parties, namely medical personnel and patients, along with applicable legal education. With regulatory reform and more transparent law enforcement, the results are expected to improve the quality of health services, protect medical personnel in carrying out their duties, and strengthen public confidence in the legal system in the health sector. This research contributes to thinking about the importance of coordination between legal institutions, medical practitioners, and the community in building a fairer system in the health care sector.